Modeling and optimization of angular misalignment effects in resonant inductive wireless power transfer for electric vehicle charging - Samshul Munir Muhamad; Wan Muhamad Hakimi Wan Bunyamin; Rahimi Baharom (Institute of Advanced Engineering and Science, 2026)
This paper presents an enhanced electromagnetic modeling and optimization study on the effects of angular misalignment in resonant inductive wireless power transfer (RIWPT) systems for electric vehicle (EV) charging. A detailed 3D model of a double-layer circular coil was developed in CST Studio Suite to investigate coupling degradation, energy loss, and efficiency behavior under angular deviations ranging from 0° to 25°, at a fixed air gap of 30 mm. Performance metrics including mutual inductance, magnetic field distribution, power transfer efficiency (PTE), and loss characteristics were analyzed to establish quantitative misalignment correlations. Results indicate a steady reduction in PTE from 99.979% at 0° to 88.441% at 25°, accompanied by corresponding increases in field asymmetry and energy dissipation. To mitigate these losses, an impedance-tuning strategy was applied by jointly optimizing transmitter-side series and parallel compensation capacitors, which improved PTE at 5° misalignment from 98.777% to 99.801%, restoring near-resonant operation. Additional analyses evaluated thermal impact, material robustness, and dynamic misalignment effects, providing a more holistic understanding of real-world charging scenarios. The study further discusses real-time tuning feasibility using embedded controllers and aligns performance with SAE J2954 and IEC standards for EV wireless charging. The findings establish validated design guidelines and adaptive tuning frameworks for achieving high-efficiency, misalignment-tolerant RIWPT systems, contributing toward robust and energy-efficient EV charging infrastructure.